2009
DOI: 10.1126/science.1176170
|View full text |Cite
|
Sign up to set email alerts
|

Mindblind Eyes: An Absence of Spontaneous Theory of Mind in Asperger Syndrome

Abstract: Adults with Asperger syndrome can understand mental states such as desires and beliefs (mentalizing) when explicitly prompted to do so, despite having impairments in social communication. We directly tested the hypothesis that such individuals nevertheless fail to mentalize spontaneously. To this end, we used an eye tracking task that has revealed the spontaneous ability to mentalize in typically-developing infants. We showed that, like infants, neurotypical adults' (N = 17) eye movements anticipated an actor'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

38
583
5
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 625 publications
(631 citation statements)
references
References 29 publications
38
583
5
5
Order By: Relevance
“…As expected and in line with a great body of literature (Happé and Frith 1996;Hill and Frith 2003;Senju 2013), individuals with ASD scored significantly lower on the direct and indirect task than the TD comparison group, with more impaired individuals scoring lower than less impaired individuals. In contrast to our expectations, which were based on previous studies (Senju et al 2009;Callenmark et al 2013), we did not find an interaction between task and group, suggesting that individuals with ASD were not more impaired in implicit than in explicit mentalizing. Both previous studies showed that individuals with ASD had impairments in implicit, spontaneously occurring mental state inferences, although they were capable of explicit mentalizing.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…As expected and in line with a great body of literature (Happé and Frith 1996;Hill and Frith 2003;Senju 2013), individuals with ASD scored significantly lower on the direct and indirect task than the TD comparison group, with more impaired individuals scoring lower than less impaired individuals. In contrast to our expectations, which were based on previous studies (Senju et al 2009;Callenmark et al 2013), we did not find an interaction between task and group, suggesting that individuals with ASD were not more impaired in implicit than in explicit mentalizing. Both previous studies showed that individuals with ASD had impairments in implicit, spontaneously occurring mental state inferences, although they were capable of explicit mentalizing.…”
Section: Discussioncontrasting
confidence: 99%
“…More specifically, both studies used highly structured and static direct tasks and unstructured, more dynamic indirect tasks. For example, in the study by Senju et al (2009) aberrant implicit mentalizing processing was inferred from a lack of visual attention anticipating where a protagonist in a film clip would look for a hidden object. In contrast, the direct mentalizing tasks used in this study assessed whether participants were able to pass static false belief tasks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…H with autism fail to show predictive gaze (Senju et al, 2009). In a recent study where participants saw rational and irrational actions, Vivanti et al (2011) demonstrated that both typically developing adolescents and adolescents with ASC orient to the face of an actor more after seeing an irrational action.…”
Section: Introductionmentioning
confidence: 99%